Inflamed target tissue provides a specific niche for highly expanded T-cell clones in early human autoimmune disease. Issue 6 (31st January 2012) - Klarenbeek, P L; de Hair, M J H; Doorenspleet, M E; van Schaik, B D C; Esveldt, R E E; van de Sande, M G H; Cantaert, T; Gerlag, D M; Baeten, D; van Kampen, A H C; Baas, F; Tak, P P; et al.
Abstract : Objective: To profile quantitatively the T-cell repertoire in multiple joints and peripheral blood of patients with recent onset (early) or established rheumatoid arthritis (RA) using a novel next-generation sequencing protocol to identify potential autoreactive clones. Methods: Synovium of patients with recent onset (early) RA (<6 months) (n=6) or established RA (>18 months) (n=6) was screened for T-cell clones by sequencing over 10 000 T-cell receptors (TCR) per sample. T cells from paired blood samples were analysed for comparison. From two patients synovial T cells were obtained from multiple inflamed joints. The degree of expansion of each individual clone was based on its unique CDR3 sequence frequency within a sample. Clones with a frequency of over 0.5% were considered to be highly expanded clones (HEC). Results: In early RA synovium, the T-cell repertoire was dominated by 35 HEC (median, range 2–70) accounting for 56% of the TCR sequenced. The clonal dominance in the synovium was patient specific and significantly greater than in established RA (median of 11 HEC (range 5–24) in established RA synovium accounting for 9.8% of T cells; p<0.01). 34% (range 28–40%) of the most expanded T-cell clones were shared between different joints in the same patients, compared with only 4% (range 0–8%) between synovium and blood (p=0.01). Conclusions: In RA, a systemic autoimmune disease, the inflamed synovium forms a niche for specific expanded T-cell clones, especially in early disease. This suggests that, at least in RA, autoreactive T cells should be addressed specifically in the inflamed tissue, preferably in the early phase of the disease.